The state of food and agriculture 2002. (Rome FAO, 2002)
Reports on current developments and issues in world agriculture. Monitors the global agricultural situation as well as the overall economic environment surrounding world agriculture. Presents and overview of the status of negotiations on agricultural trade following the launching of the World Trade Organization's new round of multilateral trade negotiations. Discusses how public goods such as agriculture, fisheries and forestry properly managed can provided benefits to large sections of people. Calls for increased international inflow of funds towards agriculture and rural areas, in order to promote globally the provision of these public goods.
"Included in this issue is the SOFA 2002 CD-ROM, containing time series data for 150 countries, country groups and regions in English, French and Spanish, together with FAOSTAT TS software to ensure easy access and use"--P. [4] of cover.
System requirements: IBM PC or compatible; minimum of 640K; DOS 3.1 or later; CD-ROM extensions (version 2.0 or later); CD-ROM drive.
Keywords: Agriculture -- Economic aspects; Carbon sequestration -- Economic aspects; Food production; Produce trade; Public goods -- Economic aspects